Clinical Heterogeneity Among LRRK2 Variants in Parkinson's Disease: A Meta-Analysis - Shu, Li; Zhang, Yuan; Pan, Hongxu; Xu, Qian; Guo, Jifeng; Tang, Beisha; Sun, Qiying (Frontiers in Aging Neuroscience, 2018)
Background: Parkinson's disease (PD) is one of the most common neurodegenerative diseases. Variants in the LRRK2 gene have been shown to be associated with PD. However, the clinical characteristics of LRRK2-related PD are heterogeneous. In our study, we performed a comprehensive pooled analysis of the association between specific LRRK2 variants and clinical features of PD. Methods: Articles from the Medline, Embase, and Cochrane databases were included in the meta-analysis. Strict inclusion criteria were applied, and detailed information was extracted from the final original articles included. Revman 5.3 software was used for publication biases and pooled and sensitivity analyses. Results: In all, 66 studies having the clinical manifestations of PD patients with G2019S, G2385R, R1628P, and R1441G were included for the final analysis. The prominent clinical features of LRRK2-G2019S-related PD patients were female sex, higher rates of early-onset PD (EOPD), and family history (OR: 0.77 [male], 1.37, 2.62; p < 0.00001, 0.02, < 0.00001). PD patients with G2019S were more likely to have high scores of Schwab & England (MD: 1.49; p < 0.00001), low GDS scores, high UPSIT scores (MD: 0.43, 4.70; p = 0.01, < 0.00001), and good response to L-dopa (OR: 2.33; p < 0.0001). Further, G2019S carriers had higher LEDD (MD: 115.20; p < 0.00001) and were more likely to develop motor complications, such as dyskinesia and motor fluctuations (OR: 2.18, 2.02; p < 0.00001, 0.04) than non-carriers. G2385R carriers were more likely to have family history (OR: 2.10; p = 0.007) than non-G2385R carriers and lower H-Y and higher MMSE scores (MD: −0.13, 1.02; p = 0.02, 0.0007). G2385R carriers had higher LEDD and tended to develop motor complications, such as motor fluctuations (MD: 53.22, OR: 3.17; p = 0.01, < 0.00001) than non-carriers. Other clinical presentations did not feature G2019S or G2385R. We observed no distinct clinical features for R1628P or R1441G. Our subgroup analyses in different ethnic group for specific variant also presented with relevant clinical characteristics of PD patients. Conclusions: Clinical heterogeneity was observed among LRRK2-associated PD in different variants in total and in different ethnic groups, especially for G2019S and G2385R.